THE EFFECT OF TEXT CHAT ON THE GROWTH OF VOCABULARY AND GRAMMAR FOR STUDENTS OF ENGLISH AS A FOREIGN LANGUAGE - Lecturer, Amal Sabbar Julaid (Journal Park Publishing, 2024)
The aim of this study was to examine the use of text chat in measuring its effect on the vocabulary and grammatical growth of EFL learners. The study sample consisted of 50 students from the English Language Department, College of Education, from the academic year 2023/2024. There were two groups, the initial group comprised 25 students, selected as the experimental group, whereas the second group also consisted of 25 students. It was assigned as the control group. The data was gathered within a span of 10 weeks. The pre-test and post-test comprise materials from Oxford University Press. The institution referred to is the University of Cambridge Local Examinations. Syndicate assesses the proficiency of non-native English language learners. In order to assess the impact of utilizing mobile text chat on the accuracy of English as a Foreign Language (EFL) learners, both groups of students took a test at the start of the 2023/2024 academic year to establish their proficiency level before to commencing the experiment. After a period of ten weeks, the identical test was given as a posttest. The study findings revealed that the experimental group outperformed the control group in terms of linguistic correctness due to the utilization of the text chat teaching approach. In addition, the results of the study showed that the experimental group students developed their vocabulary and grammar aspects. This may be due to the effect of text chat through which students in the experimental group interact with each other using texts. Accordingly, a set of recommendations were presented for those interested in the field of English as a foreign language.
Keywords: Text Chat, Proficiency, Language vocabulary, Grammar.